Dextran - The Polysaccharide With Versatile Uses - A.LAKSHMI BHAVANI; J.NISHA (International Journal of Pharma and Bio Sciences, 2010)
Dextran is the collective term given to a group of bacterial polyglucan composed of chains of D – glucose units connected by alpha – (1 -6) linkages. These polysaccharides are synthesized by a number of bacterial species. The synthesis occurs extracellularly and are catalyzed by a speciesspecific enzyme, dextransucrase. Dextran is produced at the industrial level by the fermentation of sucrose rich media. Yield of the product depends on various factors like temperature, pH and nitrogen source. Dextran is commercially available and it is used as drugs, especially as blood plasma volume expander. It has found industrial application in food, pharmaceutical and chemical industries as adjuvant, emulsifier, carrier and stabilizer. In food industry dextran is currently used as thickener for jam and ice-cream. It prevents crystallization of sugar, improves moisture retention and maintains flavor and appearance of various food items.